Extrapyramidal symptoms in schizophrenia: evidence of blunted cerebral hemodynamics during a planning task - Schüpbach, Daniel; Herpertz, Sabine (International clinical psychopharmacology, 2017)
Acute extrapyramidal symptoms (EPS) occur frequently in schizophrenia, mostly caused by antidopaminergic substances. There have been no published reports on the impact of acute EPS on cerebral blood flow (CBF) or related measures. In the following study, we examined schizophrenic patients with and without EPS during a planning task and measurements of CBF velocity. Sixteen patients with chronic schizophrenia and 16 healthy participants performed a planning paradigm during bilateral functional transcranial Doppler sonography of the middle cerebral arteries. Patients with acute EPS showed blunted CBF velocity exclusively during difficult planning tasks, and correlation analyses confirmed that higher EPS scores were associated with reduced adaption of CBF velocity. EPS in schizophrenia are associated with a detrimental effect on CBF velocity. Hypothetically, compromised adaptation of cerebral hemodynamics during difficult, but not during easy planning tasks is one correlate of dysfunctional frontostriatal circuits in schizophrenic patients with EPS.
Gesehen am 16.04.2018